Ecosystem services perspective in Green Infrastructure: a literature review - Md Sahak, Nursah‘aidah; Mohd Yunos, Mohd Yazid; Maulan, Suhardi; Ismail, Nor Atiah (2018)
The concept and application of Green Infrastructure (GI) is promptly becoming world‘s conservation and planning outline at various level of the development of nations. It is a strategic approach to build sustainable urban development by tackling the current urbanization and over population pressures and problems on urban GI resources, which are the challenges that faces our cities and towns. As a result, GI provides social and ecological responses in the broader sense of the term to help decision makers on the development of urban planning and conservation activity. GI has the potential to achieve sustainability and resilience goals over a range of outcomes in addition to climate adaptation. Therefore, the main objective of this review document is to examine the existing experience of GI planning and development activities using ecosystem services perspective throughout the world. There are a number of articles and publications which are discussed about different perspectives of GI at different level. This paper demonstrates a structured and general definition of GI, which is collected from various authors and list of ecosystem services that can be provided for GI planning and development. The paper also examines different elements that can contribute to GI network in a city by using ecosystem services that can be used by different urban planners in the future as baseline information.